2016
DOI: 10.1111/1460-6984.12240
|View full text |Cite
|
Sign up to set email alerts
|

The Sally-Anne test: an interactional analysis of a dyadic assessment

Abstract: Children's responses in the test might not be solely indicative of socio-cognitive capacities but also show orientation to interactional nuances. The study proposes that children can demonstrate diverse ways of responding to questions, yet testers may treat these as test-irrelevant behaviours if they do not correspond to the scoring criteria. A video-based CA study can broaden our understanding of children's pragmatic competencies in responsiveness that may not always embody an expected form. This can have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…A recent study of children with communication disorders investigated the interactional mechanisms involved in the administration of the Sally–Anne task (Korkiakangas et al 2016 ). The authors concluded that it is often difficult to separate the child’s performance on the FB-task from other abilities such as sensitivity to interactional nuances/signals given by the test leader, but also that the interactional skills of the test person him/herself affect the results.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of children with communication disorders investigated the interactional mechanisms involved in the administration of the Sally–Anne task (Korkiakangas et al 2016 ). The authors concluded that it is often difficult to separate the child’s performance on the FB-task from other abilities such as sensitivity to interactional nuances/signals given by the test leader, but also that the interactional skills of the test person him/herself affect the results.…”
Section: Introductionmentioning
confidence: 99%
“…The Sally-Anne test is the most commonly used firstorder false belief test to examine understanding of ToM. 4,24,25 The test presents a scenario in which Sally places a marble in a basket and leaves the room; Anne then comes in and moves the marble to a box. When Sally returns, subjects are asked the belief question, 'Where will Sally look for her marble?'…”
Section: Sally-anne Testmentioning
confidence: 99%
“…Theory of mind (ToM) is the understanding of how other people think and feel [6]. Autistic children lack theory of mind so that means they cannot understand what other people think and feel.…”
Section: Introductionmentioning
confidence: 99%